2014
DOI: 10.1038/ncomms6540
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol mediates regulation of TASK potassium channels by Gq-coupled receptors

Abstract: The two-pore domain potassium (K2P) channels TASK-1 (KCNK3) and TASK-3 (KCNK9) are important determinants of background K þ conductance and membrane potential. TASK-1/3 activity is regulated by hormones and transmitters that act through G protein-coupled receptors (GPCR) signalling via G proteins of the Ga q/11 subclass. How the receptors inhibit channel activity has remained unclear. Here, we show that TASK-1 and -3 channels are gated by diacylglycerol (DAG). Receptor-initiated inhibition of TASK required the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 56 publications
0
73
0
Order By: Relevance
“…Acute stimulation results from increased activity of StAR (222), mediated by a cascade of events which lead to calcium influx (477). These include 1) activation of phospholipase C (PLC) which hydrolyzes phosphatidylinositol-4,5-bisphosphate (PIP 2 ) into inositol 1,4,5-trisphosphate (IP 3 ) and diacylglycerol (DAG) (52,174), 2) DAG-induced inhibition of TWIK-related acid sensitive K ϩ (TASK or "leak") potassium channels which normally serve to maintain the resting membrane potential (298,561), 3) membrane depolarization, and 4) influx of calcium across the cell membrane via voltage-dependent long lasting (L)-and transient (T)-type calcium channels (37,174), which are present in roughly equal quantities within the ZG layer of the normal human adrenal cortex (143). An IP 3 -induced efflux of calcium from the ER also contributes to the rise in intracellular calcium, which leads to activation of calcium/calmodulin-dependent protein kinases (CaMK) (173,398) and ultimately activation by CaMK of cAMP-response element binding protein (CREB) which promotes StAR activity (482).…”
Section: B Regulation By Renin/ang IImentioning
confidence: 99%
“…Acute stimulation results from increased activity of StAR (222), mediated by a cascade of events which lead to calcium influx (477). These include 1) activation of phospholipase C (PLC) which hydrolyzes phosphatidylinositol-4,5-bisphosphate (PIP 2 ) into inositol 1,4,5-trisphosphate (IP 3 ) and diacylglycerol (DAG) (52,174), 2) DAG-induced inhibition of TWIK-related acid sensitive K ϩ (TASK or "leak") potassium channels which normally serve to maintain the resting membrane potential (298,561), 3) membrane depolarization, and 4) influx of calcium across the cell membrane via voltage-dependent long lasting (L)-and transient (T)-type calcium channels (37,174), which are present in roughly equal quantities within the ZG layer of the normal human adrenal cortex (143). An IP 3 -induced efflux of calcium from the ER also contributes to the rise in intracellular calcium, which leads to activation of calcium/calmodulin-dependent protein kinases (CaMK) (173,398) and ultimately activation by CaMK of cAMP-response element binding protein (CREB) which promotes StAR activity (482).…”
Section: B Regulation By Renin/ang IImentioning
confidence: 99%
“…However, we recently showed that TASK channels are not sensitive to physiological reductions of PI(4,5)P 2 concentrations (Lindner et al, 2011), but instead are regulated by the build-up of DAG resulting from activity of PLC␤ (Wilke et al, 2014). Thus, receptor-triggered inhibition of TASK channels involves PI(4,5)P 2 as the substrate for generating the messenger DAG, but in this case neuronal excitability is not regulated by PI(4,5)P 2 dynamics.…”
Section: Modulation Of Neural Excitability Via Plc-coupled Metabotropmentioning
confidence: 99%
“…Therefore, it is highly advisable to include a positive control for the efficacy of U73122 under the given experimental setting, e.g. by using a fluorescent PI(4,5)P 2 sensor as an indicator of PLC activity (Schiekel et al, 2013;Wilke et al, 2014).…”
Section: Plcmentioning
confidence: 99%
See 1 more Smart Citation
“…TASK-1 and TASK-3 are insensitive to intracellular pH, but are inhibited upon activation of G-protein-coupled receptors via a direct effect of diacylglycerol at a C-terminal domain (Wilke et al, 2014); however, the affected gating process is unknown.…”
Section: Task-2 and The K 2p Channel Gating Hypothesesmentioning
confidence: 99%